2012
DOI: 10.1111/j.1365-2567.2012.03619.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of nuclear factor‐κB responses by the S100A9 protein is Toll‐like receptor‐4‐dependent

Abstract: SummaryInteractions between danger-associated molecular patterns (DAMP) and pathogen-associated molecular patterns (PAMP) and pattern recognition receptors such as Toll-like receptors (TLRs) are critical for the regulation of the inflammatory process via activation of nuclear factor-jB (NF-jB) and cytokine secretion. In this report, we investigated the capacity of lipopolysaccharide (LPS) -free S100A9 (DAMP) protein to activate human and mouse cells compared with lipoprotein-free LPS (PAMP). First, we showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
93
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(107 citation statements)
references
References 51 publications
13
93
0
Order By: Relevance
“…For isolated MRP14, similar findings were found. Although it could be shown that MRP14 binds to both receptors TLR4 as well as RAGE (19), cytokine induction could only be observed for MRP14-TLR4-dependent activation in a cell line culturing model (39). Studies on phagocytes from TLR4 mutant mice clearly indicate that TLR4 is mainly responsible for MRP8-dependent activation in these cells (9).…”
Section: Discussionmentioning
confidence: 99%
“…For isolated MRP14, similar findings were found. Although it could be shown that MRP14 binds to both receptors TLR4 as well as RAGE (19), cytokine induction could only be observed for MRP14-TLR4-dependent activation in a cell line culturing model (39). Studies on phagocytes from TLR4 mutant mice clearly indicate that TLR4 is mainly responsible for MRP8-dependent activation in these cells (9).…”
Section: Discussionmentioning
confidence: 99%
“…Binding of S100A8 and S100A9 to TLR-4 leads to the activation of NF-jB and secretion of inflammatory cytokines in murine BMC and THP-1 cells [6,19]. In addition, studies have reported important roles for S100A8, S100A8/A9 and S100A9 in the regulation of cytokine secretion by monocytes [15,19,20]. However, only one study reported an effect of S100A8 on the secretion of IL-8 and IL-16 by human neutrophils [21].…”
Section: Discussionmentioning
confidence: 99%
“…68 In contrast, TLR4 is implicated in monocyte and DC activation by S100A9. 81 Another study showed a requirement for Ca 2+ and Zn 2+ to achieve high-affinity S100A9 binding to TLR4/MD2, whereas S100A8/A9 binding was less. 80 S100A12 is also recently reported to activate human monocytes via TLR4 69 rather than RAGE.…”
Section: S100a8mentioning
confidence: 99%